The Impact of Green Pharmacy Practices on Sustainable Healthcare - Abdullah Hussain Abdullah Ogaili,; Ali Ahmed Ali Al Eid,; Abdurrahman Fahad Nasser Alhassan,; Sukainah Ali Taqi Al Rebh,; Layla Hussain Saleh Al Hameed,; Ahmed Ali Hassan Hajji,; Mohammed Habeeb Al Nuwaiser,; Majed Ali Aljelwah,; Jaber Mohammad Bo Khader,; Ali Huassain Ali Alkhalifah,; Ahmed Khalifa Aleiyad,; Hassan Ali Al Omran, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Sustainability in healthcare has emerged as a critical concern due to the increasing environmental, economic, and social challenges faced by healthcare systems worldwide. One key area in which sustainability can be promoted is pharmacy practice, through the implementation of "green pharmacy" practices. Green pharmacy focuses on environmentally responsible, sustainable, and eco-friendly methods in medication production, distribution, use, and disposal. This paper explores the impact of green pharmacy practices on sustainable healthcare by reviewing existing literature and evaluating the practices that promote sustainability in the pharmaceutical sector. Key areas such as resource conservation, waste management, energy efficiency, and eco-friendly drug development are discussed. The findings suggest that green pharmacy practices not only reduce the environmental footprint of healthcare services but also enhance the overall efficiency and sustainability of healthcare systems. The paper concludes with recommendations for integrating green pharmacy principles into healthcare policies and practices.